Peran Grit sebagai Moderator Hubungan Antara Ketidakamanan Kerja Dan Kepuasan Kerja Pada Karyawan Terdampak Kebijakan Covid-19 - Auliya Andina Ramadhiyanti; Alice Salendu (Universitas Nusantara PGRI Kediri, 2022)
Covid-19 has brought changes in various aspects of life, including on companies and their employees. Company implements several policies as an effort to adapt with changes. This study aims to examine the role of grit as the moderator in the relationship between job insecurity and job satisfaction on employees. The approach of this research is by quantitative with cross sectional study design, conducted by distributing online questionnaires using non-probability sampling technique. The measurement tools used, namely The Minesota Satisfaction Questionnaire (MSQ) short-form, Multidimensional Qualitative Job Insecurity Scale (MQJIS), and short grit scale (Grit-S). The population of this research is employees whose company implemented policy changes due to the Covid-19. Data analysis was carried out by correlation test and moderation test using PROCESS Hayes Model 1, with the amount of data analyzed were 748 participants. The results show significant interaction effect between job insecurity and grit on job satisfaction (b = -0.02, 95% CI [-0.04, -0.01], t=-3.09, p<0.05 ). With that, it can be concluded that grit acts as moderator in the relationship between job insecurity and job satisfaction. Further analysis found grit can attenuate negative effect of job insecurity on job satisfaction when grit is in the medium and high category.